Investigations of the molecular mechanism of diltiazem binding to human serum albumin in the presence of metal ions, glucose and urea. Issue 15 (29th August 2022) - Farsad, Sara Asadi; Haghaei, Hossein; Shaban, Mina; Zakariazadeh, Mostafa; Soltani, Somaieh
Abstract: The molecular mechanism and thermodynamic properties of the interaction between diltiazem (DTZ) and human serum albumin (HSA), has been studied in vitro using spectroscopic techniques (UV-Vis, fluorescence, FTIR), and molecular docking methods. The effect of acidic and basic pH, glucose, urea, and metal ions on the DTZ-HSA binding has been investigated as well. According to the results, there is a 1:1 interaction between DTZ and HSA, while the quenching mechanism is static up to 313 K. The apparent binding constant was 2.09 × 10 6 M −1 that indicates a strong binding between DTZ and HSA. DTZ binding was increased in acidic pH while its binding was slowly decreased in the presence of glucose, urea, and metal ions. Thermodynamic studies showed that DTZ binds to HSA via an exothermic and spontaneous reaction via hydrogen bonding and electrostatic interactions. The conformational alteration of HSA is obvious according to the FTIR study. The site marker competitive study confirmed the binding of DTZ to the warfarin binding site. Molecular docking studies showed that DTZ binds to subdomain IB (−9.22 kcal mol −1 ) and subdomain IIIA (−9.03 kcal mol −1 ) with a higher tendency. Also, the results showed that the oxygen and nitrogen atoms of hydroxyl and amino functional groups of DTZ facilitate hydrogen bond formation. Highlights: Strong binding of diltiazem to HSA was studied and confirmed by fluorescence quenching titrations. Diltiazem binding to HSA reduces in the presence of metal ions, glucose, urea and alkaline pH. Diltiazem binding to HSA is exothermic and spontaneous. Graphical Abstract: UF0001 Communicated by Ramaswamy H. Sarma